Environmental Valuation of Mobile MBBR Reactor for Wastewater Management in Non-Rural Area - Nurvita Cundaningsih; Rizka Novembrianto; Kabul Fadilah (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2026)
Domestic waste remains a problem in Ngagel Rejo Village, Surabaya City, where the community is largely composed of small medium enterprises (SMEs) food traders. This study aims to assign an economic value to domestic waste management services that are not traded in the market. The benefits of deploying a mobile Moving Bed Biofilm Reactor (MBBR) will be estimated to determine the economic value of WWTP siting and to develop a retribution (user-fee) scheme for domestic waste management, particularly for the food waste consortium. A Contingent Valuation Method (CVM) will be used to elicit willingness to pay (WTP) from WWTP users as a measure of the non-use benefits of this public service and its role in reducing the impacts of domestic waste. The analysis yielded a mean WTP value of 3.6827 (as measured in the survey), which corresponds to a recommended fee of IDR 69,496.00 per month for domestic waste management services using a mobile MBBR reactor. Key factors influencing WTP include community commitment to environmental preservation programs and support for the program, consistent with the idea that public engagement strengthens the sustainability of environmental initiatives